Juvenile Atlantic sturgeon survival and movement in proximity to an active cutterhead suction dredge. - Matthew Balazik; Douglas Clarke (PLoS ONE)
The Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus has suffered population declines throughout its range. Many knowledge gaps exist regarding how to mitigate threats and better inform recovery efforts. This study examined survival of juveniles during their movements through river reaches undergoing channel maintenance dredging operations. During 2019 and 2020, 268 (30-71cm fork length) juvenile Atlantic Sturgeon were captured and released in proximity to an active cutterhead suction dredge at three sites within the James River, Virginia. Juveniles were captured, some presumed feeding, around 95-145m from the dredge in areas that could easily be avoided if the dredge created a stressful environment. No significant trends in catch-per-unit-effort were found when trawl catch was compared to a reference location or when monitoring gill net catch 100m down current of a dredge over a month-long period at one of the sites. Twenty-nine of the 229 gill net captures were implanted with acoustic tags and telemetry was used to track their movements throughout the river. Four telemetered juveniles tagged prior to this project were also detected moving within dredge operations. Cumulatively, tagged juveniles made at least 125 passes of the dredging operations with no evidence of mortality. All tagged juveniles still within the river were detected following the cessation of dredging. The results of this study support that age 1-2yr Atlantic Sturgeon show no avoidance behavior of areas 100m of an active cutterhead suction dredge and move past dredge operations with low-risk of mortality.